The Impact of Financial Management on the Growth of Small and Medium Enterprise. A Case Study Angatel Micro Finance, Soroti District - Sandra Atai (Uganda Christian University, 2024)
This study aimed to investigate the factors influencing the management of Small and Medium Enterprises (SMEs) in Soroti District, Eastern Province, Uganda, using a cross-sectional survey research design. The research employed a quantitative approach to ensure reliability and objectivity in testing theories and generalizing findings. The study focused on 80 SMEs selected from a total of 100 registered businesses, including secretarial bureaus, restaurants, stationery shops, bars, boutiques, salons, and retail shops. A stratified sampling method was utilized to ensure representation from various business categories, reducing data collection and analysis costs. Data was gathered through questionnaires distributed to SME owners or managers, with both primary data from these questionnaires and secondary data from reports, research works, and online resources being used. The validity of the research instrument was confirmed through expert reviews and the calculation of the Content Validity Index (CVI), aiming for a CVI of 0.7 and above. Reliability was assessed using Cronbach’s coefficient alpha, with a pilot study conducted to refine the instrument. Data collection involved distributing questionnaires after obtaining approval from Uganda Christian University and relevant authorities. The questionnaires were systematically collected, sorted, and coded for analysis. Quantitative data was analyzed using SPSS version 20, employing descriptive statistics and Pearson Correlation to examine relationships between variables. Ethical considerations included obtaining consent from respondents and citing all sources used. Anticipated limitations involved potential funding constraints, respondent reluctance, and delays in data collection. Strategies were implemented to address these limitations, including seeking financial support and issuing additional questionnaires.
Undergraduate Research